The effect of clay type and solid wettability on bitumen extraction from Canadian oil sands. (1st April 2023) - Li, An; Li, Rui; Yan, Ci; Wang, Han; Liu, Qingxia; Masliyah, Jacob H.; Zeng, Hongbo; Xu, Zhenghe
Graphical abstract: Highlights: Hydrophilic clays had a significant depression on bitumen recovery. Hydrophobic clays exhibited a serious deterioration in froth quality. Clay mineralogy was negligible after coverage of organic contaminants. Slime-coating of clays on bitumen occurred above a threshold clay concentration. Kaolinite was confirmed to slime-coat on bitumen surface the first time. Abstract: Clays (<2 μm) in oil sands ores have a significant impact on the processability of the ores. The present study aims at understanding the effects of the type and wettability of clays on the performance of bitumen extraction from mined oil sands. The results from batch extraction tests showed a detrimental effect of doping with hydrophilic clays (kaolinite, illite and montmorillonite), with montmorillonite being the worst. The crucial role of clays in bitumen slime-coating was studied through atomic force microscopy and clay deposition tests. For the hydrophilic clays, clay concentration was an essential parameter in determining the bitumen-clay hetero-coagulation process. Strong slime-coating of clay particles on bitumen droplets occurred only above a critical clay concentration. This critical concentration varied with clay type and water chemistry. Compared with earlier studies, kaolinite was found to deposit strongly on bitumen surfaces for the first time in this study. Hydrophilic clays were contaminated by soaking in toluene-diluted-bitumen solutions to investigate the effect of solid hydrophobicity on bitumen extraction. Hydrophobic clays had a less significant depression on bitumen recovery but a more significant deterioration on froth quality than hydrophilic clays. Similar slime-coating was observed for the different clays once contaminated by diluted bitumen. Furthermore, the presence of a large content of clays in bitumen extraction could result in excessive emulsification of bitumen into small droplets, leading to low bitumen recovery. This work provides useful insights into the fundamental interactions of clays and bitumen, with implications for developing a viable solution in dealing with clays in oil sands operations.